2023
DOI: 10.1371/journal.pone.0284964
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the maternal-fetal interface and vertical transmission following low-dose inoculation of pregnant rhesus macaques (Macaca mulatta) with an African-lineage Zika virus

Abstract: Background Congenital Zika virus (ZIKV) infection can result in birth defects, including malformations in the fetal brain and visual system. There are two distinct genetic lineages of ZIKV: African and Asian. Asian-lineage ZIKVs have been associated with adverse pregnancy outcomes in humans; however, recent evidence from experimental models suggests that African-lineage viruses can also be vertically transmitted and cause fetal harm. Methodology/Principal findings To evaluate the pathway of vertical transmis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…We hypothesize that in the viral non-controllers ZIKV reaches this site by 7 DPI, when infectious virus is still detectable in the maternal blood, and that establishment of this viral reservoir leads to the prolonged plasma vRNA burden and increased vRNA burden in the MFI that is observed. This is consistent with a recent report that ZIKV is able to reach the MFI tissues as early as 7 DPI ( 60 ). Maternal plasma vRNA burden was cleared prior to delivery in all dams regardless of the level of vRNA burden in the MFI tissues at delivery.…”
Section: Discussionsupporting
confidence: 94%
“…We hypothesize that in the viral non-controllers ZIKV reaches this site by 7 DPI, when infectious virus is still detectable in the maternal blood, and that establishment of this viral reservoir leads to the prolonged plasma vRNA burden and increased vRNA burden in the MFI that is observed. This is consistent with a recent report that ZIKV is able to reach the MFI tissues as early as 7 DPI ( 60 ). Maternal plasma vRNA burden was cleared prior to delivery in all dams regardless of the level of vRNA burden in the MFI tissues at delivery.…”
Section: Discussionsupporting
confidence: 94%
“…Evidence for the transplacental route of ZIKV vertical transmission is currently sparse in human cases of congenital ZIKV infection and non-human primate (NHP) in vivo studies. To our knowledge, there are no published results that show STB infection in cases of human congenital ZIKV infection, and ZIKV has rarely been found in STBs in NHP studies [11][12][13][14][15]. Reports of the vulnerability of STBs and CTBs to infection have primarily been obtained from ex vivo or in vitro studies using both Asian and African-lineage ZIKV.…”
Section: Introductionmentioning
confidence: 99%
“…Once the chorionic membrane is infected, the fetus is no longer protected by trophoblasts and ZIKV can, theoretically, easily spread to fetal vessels in the chorionic plate and into the amniotic fluid. Substantial evidence supports that the fetal membranes are susceptible to ZIKV infection [10,11,14,15,17,[22][23][24][25][26][27]. The fetal membranes have been found to be infected in a human case of congenital ZIKV infection that resulted in a miscarriage [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another in vivo study investigating the effect of low-dose Zika virus in rhesus macaques showed that this virus does not have a substantial effect on the placenta. 177 Moreover, no clinical studies have reported an association between this virus and hypertensive disorder during pregnancy. Therefore, future studies are required to establish the link between preeclampsia and Zika virus infection.…”
Section: Zika Virusmentioning
confidence: 99%